Perbandingan Sistem Perlindungan Hukum Medis (PMH) Studi Kasus Indonesia dan Korea Selatan Dalam Konteks Tenaga Kesehatan - Keisha Zahra Wibowo; Dinda Aurelia Rosi Nasution; Najla Azrijal Chosaf; Marcello Putra Toding Palilli; Syamhaikel Pavel Budiman; Nimrod Welly Belo (Yayasan pendidikan dzurriyatul Quran, 2025)
Medical legal protection is a crucial aspect in the world of healthcare, particularly amidst the rapid development of healthcare services and the increasing demand for ethical and legal professional services. Healthcare workers are the frontline workers who deal directly with patients, therefore an adequate legal protection system not only guarantees patient rights but also provides a sense of security and justice for healthcare workers in carrying out their duties. The purpose of this study was to compare medical legal protection systems. The research method used in this study was a literature review method. The results indicate that medical legal protection is an important foundation that every country must have to ensure the safety of healthcare workers and the quality of services to patients. From the comparison between Indonesia and South Korea, it is clear that although both have a high awareness of legal protection for healthcare workers, its implementation and mechanisms operate differently according to the social, cultural, and legal conditions of each country.